2022
DOI: 10.1038/s41597-022-01605-x
|View full text |Cite
|
Sign up to set email alerts
|

A global dataset for prevalence of Salmonella Gallinarum between 1945 and 2021

Abstract: Pullorum disease and fowl typhoid are among the most significant poultry diseases worldwide. However, the global burden of these diseases remains unknown. Most importantly, the parameters contributing to the prevalence of Salmonella Gallinarum variants are not well documented. Therefore, in this study, we present a systematic review and meta-analysis of the global prevalence of Salmonella Gallinarum during 1945–2021. In total, 201 studies were identified for qualitative analysis (>900 million samples). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
(18 reference statements)
0
27
0
Order By: Relevance
“…Our results showed a high level of contamination along the poultry production chain, especially in the market, which could be a potential risk for consumers. No isolate was found in the samples collected from breeding farms, possibly because positive samples were few, and most of the contaminations were caused by Salmonella Gallinarum biovar Pullorum, which are highly avian-adapted and grew too slow to be isolated in selective enrichment medium used during the sampling periods ( 22 ). Due to dominance of S .…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed a high level of contamination along the poultry production chain, especially in the market, which could be a potential risk for consumers. No isolate was found in the samples collected from breeding farms, possibly because positive samples were few, and most of the contaminations were caused by Salmonella Gallinarum biovar Pullorum, which are highly avian-adapted and grew too slow to be isolated in selective enrichment medium used during the sampling periods ( 22 ). Due to dominance of S .…”
Section: Resultsmentioning
confidence: 99%
“…S. Pullorum, causing Pullorum disease in poultry, is an important pathogen in great need of control and disease eradication [ 3 , 5 , 9 ]. Nevertheless, the mechanism of how S. Pullorum targets and continuously colonizes the host’s organs remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous meta-analysis showed that S . Pullorum is still very common in many regions, especially in developing countries [ 9 ], although it has been the target of disease eradication schemes in most industrialized countries [ 2 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Thus, the diverse LSs also show various and signicant biological activities, such as anti-inammation, [40][41][42][43] antitumor, [44][45][46] and anti-infection. [47][48][49][50] In particular, 13 ′ -Omethyl succinylshizukaol C has been reported to show about 1000-fold stronger antimalarial activity than that of artemisinin. 48,50 Considering their diverse skeletons and strong bioactivities, [5][6][7][8][9][10]44,45,[47][48][49][50] the total synthesis of LSs and their oligomers has also attracted signicant interest from organic chemists, and thus far, complex and bioactive oligomers with seven types of skeletons have been synthesized by several groups.…”
Section: Introductionmentioning
confidence: 99%